(untitled) (The Journal of Plant Protection Sciences, 2022)
Mulberry (Morus alba L.) is grown for its foliage India. Thrips incidence prevails in mulberry eco to feed the silkworm, (Bombyx mori L.) for silk system during February-June. Over 22 species production. In India 1.84 lakh ha is under were reported to infest mulberry (15,16,17) mulberry cultivation of which 30935 ha are in among which Pseduodendrothrips mori is West Bengal (1).